2012
DOI: 10.1001/archinternmed.2011.1031
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Eating Index and Mortality in a Nationally Representative Elderly Cohort

Abstract: joyment in the present analyses. But greater enjoyment was associated with a 28% lower risk of death even after these factors, as well as depression and health behaviors, had been taken into account. Other factors may be responsible for the remaining association between enjoyment and survival. It may be caused by unmeasured confounding factors such as other pre-existing illnesses. Only 3 health behaviors were assessed, and other aspects such as diet may be relevant. In addition, direct links with health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
1
25
2
1
Order By: Relevance
“…In several studies, adherence to the HEI has been associated with lower chronic disease risk (45)(46)(47) , and whereas adherence to the HEI-1995 was associated with a 30% reduction in mortality risk in males, this relationship was not apparent in females (48) . For those aged 65+ years, a higher HEI-1995 score was associated with lower overall and cardiovascular mortality irrespective of gender (49) . The Recommended Food Score developed by Kant et al (50) is a composite measure based on the sum of the number of foods recommended by the current dietary guidelines (fruit, vegetables, whole grains, low-fat dairy and lean meats and poultry) that were reported to be consumed at least once weekly and higher scores were associated with lower risk of all-cause mortality (28 and 18% lower risk in men and women, respectively) (50,51) .…”
Section: Myocardial Infarctionmentioning
confidence: 88%
“…In several studies, adherence to the HEI has been associated with lower chronic disease risk (45)(46)(47) , and whereas adherence to the HEI-1995 was associated with a 30% reduction in mortality risk in males, this relationship was not apparent in females (48) . For those aged 65+ years, a higher HEI-1995 score was associated with lower overall and cardiovascular mortality irrespective of gender (49) . The Recommended Food Score developed by Kant et al (50) is a composite measure based on the sum of the number of foods recommended by the current dietary guidelines (fruit, vegetables, whole grains, low-fat dairy and lean meats and poultry) that were reported to be consumed at least once weekly and higher scores were associated with lower risk of all-cause mortality (28 and 18% lower risk in men and women, respectively) (50,51) .…”
Section: Myocardial Infarctionmentioning
confidence: 88%
“…Studies have been conducted examining various dietary patterns and indices in relation to mortality [60][61][62]. In the NHANES III cohort study, the HEI was found to be inversely associated with overall and CVD mortality [61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted examining various dietary patterns and indices in relation to mortality [60][61][62]. In the NHANES III cohort study, the HEI was found to be inversely associated with overall and CVD mortality [61]. In a study conducted in the National Institutes of Health-AARP Diet and Health Study, the Mediterranean diet score was associated with reduced all-cause and cause-specific mortality [60], while another report from the National Institutes of Health-AARP Diet and Health Study showed various indices [HEI-2010, the Alternative Healthy Eating Index-2010 (AHEI-2010), the alternate Mediterranean Diet (aMED), and Dietary Approaches to Stop Hypertension (DASH)] to be protective against all-cause mortality, CVD, and cancer mortality [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] One aspect of health linked to dietary choice is excess body fat. Because of this, the current health goals for Americans (Healthy People 2020) focus on improving both diet quality and weight management.…”
Section: Introductionmentioning
confidence: 99%